2007
DOI: 10.1007/s11695-007-9147-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Severity of Sleep Apnea in a Group of Morbidly Obese Patients

Abstract: There was a high frequency of sleep apnea in this group of morbidly obese patients, for whom it was very important to request polysomnography, thus enabling therapeutic management and prognostication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 24 publications
5
45
0
4
Order By: Relevance
“…17 Obstructive sleep apnea (OSA) is another common breathing disorder among the obese that, in addition to obesity-hypoventilation syndrome, must be taken into account before surgery. 18,19 …”
Section: Physiological Characteristics Of the Respiratory System Durimentioning
confidence: 99%
“…17 Obstructive sleep apnea (OSA) is another common breathing disorder among the obese that, in addition to obesity-hypoventilation syndrome, must be taken into account before surgery. 18,19 …”
Section: Physiological Characteristics Of the Respiratory System Durimentioning
confidence: 99%
“…Obesity is associated with many different comorbidities including obstructive sleep apnoea (OSA). [2][3][4][5] Worldwide, studies have found a high level of clinically undiagnosed OSA in obese patients, particularly those who are morbidly obese. 3,4,6 However, no studies have sought to establish the size of this association in clinical practice in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…7 This relationship is well documented in the literature. 8 However, there has been no previous study to quantify this association within the general population in the UK.…”
Section: -5mentioning
confidence: 99%
“…7 This relationship is well documented in the literature. 8 However, there has been no previous study to quantify this association within the general population in the UK.The study by Wall and colleagues 9 in this issue of the PCRJ is the first time the strength of association between OSA, snoring and obesity has been investigated in the UK using a large primary care database. In a cross-sectional study of records from The Health Improvement Network (THIN) database, and controlling for confounding factors such as gender, age, region, and socioeconomic status, they used logistic regression techniques to explore the relationship between body mass index (BMI), a history of snoring, and a diagnosis of OSA in the over-50s in the UK.…”
mentioning
confidence: 99%